2021
DOI: 10.3389/fpsyg.2021.629205
|View full text |Cite
|
Sign up to set email alerts
|

Psychology Doctoral Program Experiences and Student Well-Being, Mental Health, and Optimism During the COVID-19 Pandemic

Abstract: In a sample of 916 doctoral students from 144 universities across the United States, we examined psychology graduate students’ experiences in their programs, as well as their mental health, well-being, and optimism during the onset of the COVID-19 pandemic. In a path model, we found that students’ psychological experiences in their programs (i.e., social belonging, threat, and challenge) were associated with better mental health and well-being, which in turn was associated with greater optimism about the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…Analyses of the demographic predictor variables revealed that Black/African American students reported significantly greater levels of graduate student stress. These findings are consistent with previous studies that have indicated that the COVID-19 pandemic has disproportionately affected Black, Indigenous, and people of color (BIPOC) communities in the United States (Syropoulos et al, 2021). Graduate programs in psychology need to recognize and address that students of underrepresented backgrounds, such as Black/African American students, face additional challenges in graduate school that may be heightened during the pandemic.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Analyses of the demographic predictor variables revealed that Black/African American students reported significantly greater levels of graduate student stress. These findings are consistent with previous studies that have indicated that the COVID-19 pandemic has disproportionately affected Black, Indigenous, and people of color (BIPOC) communities in the United States (Syropoulos et al, 2021). Graduate programs in psychology need to recognize and address that students of underrepresented backgrounds, such as Black/African American students, face additional challenges in graduate school that may be heightened during the pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…Students proposed ideas for enhancing self-care practice such as hosting weekly self-care events, talking about self-care regularly in class, encouraging days off, respecting boundaries for emails and responses, and adjusting syllabi to reduce unnecessary work. The student’s reports are consistent with previous research on psychology doctoral students during COVID-19, suggesting that students can benefit from programs that create an encouraging environment that promotes self-care (Bamonti et al, 2014), provide students with a sense of social belonging, and reduce graduate student expectations (Syropoulos et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“… 19 Positive psychology variables are considered protective factors of mental health. 20 , 21 Self-compassion refers to being accepting and patient of oneself in the face of failures and flaws, or following a traumatic experience. 22 Self-compassion is an emotionally supportive self-attitude that may shield against the harmful effects of self-criticism, etc.…”
Section: Introductionmentioning
confidence: 99%